Analysis of the Influence of Digital Marketing on the Use of Online Social Media As A Strategy to Improve Service Quality - Wiguna, Paramita Kurnia; Losoiyo, Sylvianovelista R (GLOBAL HEALTH SCIENCE GROUP, 2024)
Digital marketing simplifies the marketing process for hospital businesses. Digital marketing provides opportunities as well as challenges for marketing management in increasing public interest in hospital products and in improving the quality of services in hospitals. With the development of the digital world, it is hoped that it can be used by hospital management as a form of marketing strategy and also to improve the quality of service. Currently, many hospitals use mobile applications to help patients find out doctor's service schedules, schedule visits, and view data on their treatment history. Objectives : The aim of this research is to analyze the influence of digital marketing as a strategy to improve service quality at referral hospitals in Maluku province. Method : The method in this research uses quantitative research using analytical observational studies with a cross sectional study design. Based on the data obtained, the data was tabulated and analyzed based on the research objectives using SPSS to describe the frequency distribution of each respondent's characteristics, variables and research dimensions, using univariate tests and bivariate tests (chi square).Results : The results of the analysis of the significant relationship regarding digital marketing with the use of online social media, obtained a significance value of 0.000 so that in this case the research hypothesis is accepted. Conclusion : So it can be concluded that there is an influence of digital marketing on the strategy to improve service quality at the Maluku Province Referral Hospital. Digital Marketing is the use of digital technology to strengthen the brand image of health facilities while making it easier for customers to find hospital locations and determine the choice or type of hospital service they want.